A single CD4 test with 250 cells/mm3 threshold predicts viral suppression in HIV-infected adults failing first-line therapy by clinical criteria - Gilks, C; Walker, A; Munderi, P; Kityo, C; Reid, A; Katabira, E; Goodall, R; Grosskurth, H; Mugyenyi, P; Hakim, J; Gibb, D (Public Library of Science, 2013)
BACKGROUND: In low-income countries, viral load (VL) monitoring of antiretroviral therapy (ART) is rarely available in the public sector for HIV-infected adults or children. Using clinical failure alone to identify first-line ART failure and trigger regimen switch may result in unnecessary use of costly second-line therapy. Our objective was to identify CD4 threshold values to confirm clinically-determined ART failure when VL is unavailable. METHODS: 3316 HIV-infected Ugandan/Zimbabwean adults were randomised to first-line ART with Clinically-Driven (CDM, CD4s measured but blinded) or routine Laboratory and Clinical Monitoring (LCM, 12-weekly CD4s) in the DART trial. CD4 at switch and ART failure criteria (new/recurrent WHO 4, single/multiple WHO 3 event; LCM: CD4<100 cells/mm(3)) were reviewed in 361 LCM, 314 CDM participants who switched over median 5 years follow-up. Retrospective VLs were available in 368 (55%) participants. RESULTS: Overall, 265/361 (73%) LCM participants failed with CD4<100 cells/mm(3); only 7 (2%) switched with CD4≥250 cells/mm(3), four switches triggered by WHO events. Without CD4 monitoring, 207/314 (66%) CDM participants failed with WHO 4 events, and 77(25%)/30(10%) with single/multiple WHO 3 events. Failure/switching with single WHO 3 events was more likely with CD4≥250 cells/mm(3) (28/77; 36%) (p = 0.0002). CD4 monitoring reduced switching with viral suppression: 23/187 (12%) LCM versus 49/181 (27%) CDM had VL<400 copies/ml at failure/switch (p<0.0001). Amongst CDM participants with CD4<250 cells/mm(3) only 11/133 (8%) had VL<400 copies/ml, compared with 38/48 (79%) with CD4≥250 cells/mm(3) (p<0.0001). CONCLUSION: Multiple, but not single, WHO 3 events predicted first-line ART failure. A CD4 threshold 'tiebreaker' of ≥250 cells/mm(3) for clinically-monitored patients failing first-line could identify ∼80% with VL<400 copies/ml, who are unlikely to benefit from second-line. Targeting CD4s to single WHO stage 3 'clinical failures' would particularly avoid premature, costly switch to second-line ART.